Towards a model-based framework for integrating usability evaluation techniques in agile software model - Butt, S.M. (Springer Verlag, 2014)
Various new agile software models were offered though agile manifesto as a counteraction to conventional and extensive software techniques and process design. SE followed a systematic approach of development. Whereas integrating usability in software development improved the ability of software product to be used, learned and be attractive to the users. Research showed the benefit of usability; yet, to this day agile software model continues to exhibit less importance of this quality attribute. Moreover, poor usability and inefficient design were the common reasons in software product failure. The aim of this paper was to develop a model to integrate usability evaluation methods into agile software model. This was done by proposing a unique model and evaluate the proposed model by using IEEE Std 12207-2008, ISO 9241:210. Â© Springer International Publishing Switzerland 2014.